2016
DOI: 10.1186/s12935-016-0277-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics inhibit sphere-forming ability in suspension culture

Abstract: BackgroundThis last decade, a lot of emphasis has been placed on developing new cancer cell culture models, closer to in vivo condition, in order to test new drugs and therapies. In the case of colorectal cancer, the use of patient biopsies to seed 3D primary cultures and mimic tumor initiation necessitates the use of antibiotics to prevent microbial intestinal contamination. However, not only long term use of antibiotics may mask the presence of low levels of microbial contamination, it may also impact cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…However, this may not apply to different cancers or even other, not assayed, RCC cell lines (41). Penicillin-streptomycin enhanced Caki-1 2D cell growth as observed previously for colon cancer cell lines (42), but its mechanism requires further analysis. The tested RCC cell lines were also insensitive to azithromycin, both the 2D and the sphere-forming population.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, this may not apply to different cancers or even other, not assayed, RCC cell lines (41). Penicillin-streptomycin enhanced Caki-1 2D cell growth as observed previously for colon cancer cell lines (42), but its mechanism requires further analysis. The tested RCC cell lines were also insensitive to azithromycin, both the 2D and the sphere-forming population.…”
Section: Discussionsupporting
confidence: 65%
“…It is also worth emphasizing that sunitinib suppresses the proliferation, migration, apoptosis resistance, tumor angiogenesis and growth of triple-negative breast cancers but increases the percentage of breast cancer stem cells in tumors (39), which is in agreement with the fact that sunitinib was recently shown in preclinical models to increase invasive and metastatic properties of breast cancer cells (40). Surprisingly, recently, several groups have reported that antibiotics, including those routinely used in cell culture, can interfere with the sphere-forming abilities of cancer cells, and therefore their impact on CSCs may be expected (41,42). Selective toxic effects on CSCs have been reported for azithromycin, chloramphenicol and doxycycline (41).…”
Section: Introductionmentioning
confidence: 99%
“…However, it also possesses some affinity to the ribosomes in eukaryotic cells. Relier and colleagues suggested that streptomycin may act on eukaryotic cells through the disruption of protein synthesis, by affecting mitochondrial activity, by binding to certain RNAs or by interfering with miRNAs action [ 12 ]. This indicates that the addition of streptomycin changes the gene expression profile in cells and it may affect the differentiation process.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and cultivation of adipose-derived stem cells usually involves the presence of the penicillin-streptomycin mixture [ 2 , 5 , 8 , 9 ] although some studies have also suggested using amphotericin B because of its widespread antifungal activity [ 10 , 11 ]. Gentamycin is also commonly used in cell cultures, although a penicillin-streptomycin (PS) mixture is the only one that is recommended by the American Type Culture Collection (ATCC) [ 12 ]. Protective/preventive antibiotic therapy improves the success/safety of transplantation procedures [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This test was performed as previously described [61]. Number of sphere forming cells were determined after plating of 100 cells / 100 µL of M11 medium (DMEM/F12 (1:1) Glutamax medium, N2 Supplement, Glucose 0.3 %, insulin 20 µg/ml, hBasic-FGF 10 ng/ml, hEGF 20 ng/ml) in ultra-low attachment 96 well-plates.…”
Section: Methodsmentioning
confidence: 99%